Pengaruh Lingkungan Kerja Dan Kompensasi Terhadap Kepuasan Kerja Karyawan: Studi Pada Divisi Marketing Bank DBS Bandung - Siti Maesaroh; Alda Ramadhika (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
Job satisfaction is very much needed by a company as a factor that can encourage and influence work enthusiasm. Job satisfaction is basically an individual thing that has different levels of satisfaction according to their desires, both in terms of the Work Environment, Work Discipline, and Compensation. The purpose of this study is to determine and analyze the influence of the Work Environment and Compensation on Job Satisfaction at Bank DBS Marketing Division. The method in this study uses a quantitative method with a descriptive and verification approach. The sample used in this study was 60 respondents. Which is to answer the formulation of the problem in this study using the SPSS 22 program. The results of the study show that: (1) Job satisfaction of Bank DBS Marketing Division employees has a category of Less Satisfied. (2) The physical and non-physical work environment at Bank DBS Marketing Division is in the satisfied category for Employees. (3) Compensation has a category of less satisfied. (4) Work Environment and Compensation have an influence on Job Satisfaction of 48.1%. In addition, the rest is influenced by other factors.